Improving the Quality of Thematic Learning through the Discovery Learning Model in Class V SDN Legok Kebasen Students - Widyastuti, Yuni (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The background of this research is the low quality of thematic learning and the use of less varied methods. The aim of this Classroom Action Research is expected to improve the quality of thematic learning through the Discovery Learning model for fifth grade students of SDN Legok Kebasen. This Classroom Action Research was conducted in 2 cycles, each cycle consisting of four stages, namely planning, implementing, observing and reflecting. The implementation of the action uses the Discovery Learning model with a systematics of initial activities, core activities and final activities. The results showed that students' learning completeness increased from 47.62% in the initial study to 66.67% in the first cycle and 90.48% in the second cycle. Student activity also increased from 23.86 in the initial study to 24.95 in the first cycle and 27.38 in the second cycle. The class average increased from 61.43 in the initial study to 70.00 in the first cycle and 75.24 in the second cycle. From the research results it can be concluded that the application of the Discovery Learning model can improve the quality of learning.